2010
DOI: 10.1007/s10689-010-9373-2
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of extracolonic tumors in Brazilian families with Lynch syndrome: analysis of a hereditary colorectal cancer institutional registry

Abstract: Lynch syndrome (LS) is caused by inherited germline mutations in mismatch repair (MMR) genes. It is one of the commonest forms of inherited predisposition to colorectal cancer (CRC), accounting for 2-5% of all CRC. LS is characterized by early age of onset, with a tendency for multiplicity and an increased risk for extra-colonic tumors at particular sites. In this study we have evaluated the frequency of extra-colonic tumors in 60 unrelated LS families fulfilling the Amsterdam criteria (ACI. ACII) from the Onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 67 publications
2
39
1
2
Order By: Relevance
“…Meanwhile, there are significant discrepancies, 33-78%, between similar studies in other countries (Park et al, 2000;Maul et al, 2006;da Silva et al, 2010;Bansidhar, 2012).…”
Section: 4647 Epidemioclinical Features Of Early-onset Colorectal Camentioning
confidence: 83%
See 1 more Smart Citation
“…Meanwhile, there are significant discrepancies, 33-78%, between similar studies in other countries (Park et al, 2000;Maul et al, 2006;da Silva et al, 2010;Bansidhar, 2012).…”
Section: 4647 Epidemioclinical Features Of Early-onset Colorectal Camentioning
confidence: 83%
“…There are, however, distinct discrepancies between Western and Eastern populations over this issue (Bansidhar, 2012). In a Brazilian study, GC was the second most common extracolonic cancer in HNPCC families (da Silva et al, 2010). In addition, several Chinese and Korean studies have presented GC as the most common extracolonic cancer in HNPCC (Park et al, 2000), while in Western populations, the prevalence of GC within HNPCC cohorts is the third or fourth most common cancer (Maul et al, 2006;Bansidhar, 2012).…”
Section: 4647 Epidemioclinical Features Of Early-onset Colorectal Camentioning
confidence: 99%
“…In the Lynch Syndrome, tumours have been known to be predominant in the proximal colon [35,36] , but recent research revealed contradictory data where the most frequent site among early onset CRC patients was the distal colon [37] . Of these, between 40 and 60 percent were in the rectum [38,39] .…”
Section: Pathologymentioning
confidence: 99%
“…Attempts have been made to directly estimate the risk of prostate cancer in Lynch syndrome using studies of cancer history of men from Lynch syndrome families (14,15,19,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). These studies have generally been limited in terms of size and analytic methods used, so as a consequence, estimates are imprecise and inconsistent.…”
Section: Introductionmentioning
confidence: 99%